Field Survey of 2021 Typhoon Rai –Odette- in the Philippines - Esteban, Miguel; Valdez, Justin; Tan, Nicholson; Rica, Ariel; Vasquez, Glacer; Jamero, Laurice; Valenzuela, Paolo; Sumalinog, Brian; Ruiz, Rex; Gera, Weena; Chadwick, Christopher; Spatarau, Catalina; et al. (Journal of Coastal and Riverine Flood Risk, 2023)
Typhoon Rai struck the Philippines on the 16th December 2021, damaging and inundating many coastal areas along the Visayas region of the country due to the high winds, storm surges and wind driven waves it generated. In order to understand the various damage mechanisms, the authors conducted a field survey to measure the storm surge heights at several locations in the provinces of Cebu and Bohol. As part of the survey, local residents were interviewed to understand the phenomena and survey the height reached by the storm surge. The maximum storm surge level measured were 2.54 m, 4.24 m and 4.06 m along the provinces of Cebu and Bohol. Finally, some interesting characteristics of the storm surge are summarised, and the lessons learnt in terms of disaster risk management are discussed